INTERPOSITION AND COLOR CONTRAST AS DEPTH ASPECT: FROM 2D MEDIA TO 3D SPACE PRODUCTION - Muvida, Muvida; Atmodiwirjo, Paramita; Paramita, Kristanti Dewi (MODUL, 2023)
This study attempts to dismantle the depth aspects produced by two-dimensional (2D) media such as paintings. as the basis for the production of three-dimensional (3D) space. In particular, we argue that painting as artwork with a flat surface can be transformed into 3D space by incorporating depth aspects. Even though it has a flat surface, painting as a 2D medium has the impression of 3D space and volume, which can be circumvented by constructing the perception of depth. To explore the production of 3D space through depth aspects, four 2D paintings were analyzed to find out how the depth aspects were constructed. The analysis reveals the perception of depth technique through interposition as the depth cues within the arrangement of layers. The analysis also reveals the color contrast as additional aspect that strengthen the perception of depth. Both the interposition and the color contrast become the important aspects that create the perception of depth in the production of the 3D space.